Thermo-voltage measurements of atomic contacts at low temperature - Ofarim, Ayelet; Kopp, Bastian; Möller, Thomas; Martin, León; Boneberg, Johannes; Leiderer, Paul; Scheer, Elke (Beilstein Journal of Nanotechnology, 2016)
We report the development of a novel method to determine the thermopower of atomic-sized gold contacts at low temperature. For these measurements a mechanically controllable break junction (MCBJ) system is used and a laser source generates a temperature difference of a few kelvins across the junction to create a thermo-voltage. Since the temperature difference enters directly into the Seebeck coefficient S = −ΔV/ΔT, the determination of the temperature plays an important role. We present a method for the determination of the temperature difference using a combination of a finite element simulation, which reveals the temperature distribution of the sample, and the measurement of the resistance change due to laser heating of sensor leads on both sides next to the junction. Our results for the measured thermopower are in agreement with recent reports in the literature.
Keywords: atomic contacts; finite element simulations; laser heating; low temperature; mechanically controllable break-junction; temperature determination; thermopower